Kriteria penggolongan kata: Bahasa Yunani, Inggeris & Melayu - Norliza Jamaluddin, (Universiti Kebangsaan Malaysia, 2008)
Words are fundamental units in every sentence. Words can be categorised into different types or ‘word classes’. This paper discusses three major criteria for word classes which are based on semantic (the meaning of the word), morphology (the form or ‘shape’ of the word) and syntactic distribution (the position or ‘environment’ of the word in a sentence). Early writings on the criteria of word classes can be traced back to the ancient era of Greek and Latin languages. During this traditional period, categorisation was mainly based on the meaning of the word. However, this categorisation was extended to include the other two criteria as it is impossible to classify words only by one single categorisation. This evolution in categorisation of word classes is adapted and developed in European languages and is also apparent in the Malay language